Penguatan Literasi Sains sebagai Instrumen Pertahanan Negara: Tinjauan Literatur Melawan Disinformasi Lingkungan dan Bencana - Triason, Herwan; Wahyudi, Bisyron; Sibarani, Frado (PendIPA Journal of Science Education, 2026)
Environmental and disaster disinformation has evolved into a serious hybrid threat to national defense, targeting social stability and public trust during crises. This study aims to analyze the strategic role of science literacy as a non-military defense modality in countering false narratives and pseudoscience. Employing a Systematic Literature Review (SLR) method with the PRISMA protocol, this study reviewed selected articles published between 2020 and 2025 from Scopus, Google Scholar, and Garuda Portal databases. The analysis reveals that disaster disinformation operates as a form of cognitive warfare that undermines national mitigation responses. Key findings confirm that science literacy functions effectively as a "cognitive shield" that enhances public resistance to hoaxes, while simultaneously repositioning critical thinking skills as a modern manifestation of the State Defense (Bela Negara) concept within the Universal People's Defense and Security System (Sishankamrata). This study concludes that integrating science curriculum with defense doctrine is imperative to build adaptive national resilience. Synergy between the education and defense sectors is recommended to create a resilient information ecosystem.